Perceived Constraints in Livestock Service Delivery by Dairy Cooperatives: A Case Study of Western Maharashtra, India - Rathod, Prakashkumar; Nikam, T R; Landge, Sariput; Hatey, Amit (Indian Journal of Dairy Science, 2012)
Livestock service delivery by Dairy Cooperatives in developing countries like India is getting attention from the past decade. However, due to competitive market players, these cooperatives are able to handle only about 17 per cent of the marketable milk surplus. Hence, there is an urgent need to study the factors hindering availability and effectiveness of livestock service delivery. Keeping this in view, an earnest effort was made to study the perceived constraints of farmers and cooperative staff in livestock service delivery of Dairy Cooperatives in Western Maharashtra. To obtain the suggestions in this regards, the study also summarized the Strengths, Weaknesses, Opportunities and Threats (SWOT) of Gokul Dairy Cooperative. A pretested interview schedule was used to collect data from 150 dairy producer members and 35 cooperative staff which included veterinarians, para-veterinarians and secretaries of village level cooperatives. The study reported that Gokul Dairy Union delivered 46 livestock services under seven heads, viz. animal health care, breeding, production and management, feed and fodder production, extension, marketing and other services. Dairy farmers and cooperative staff perceived that constraints in livestock service delivery included human resource, financial, policy related and administrative constraints. Among various constraints, high cost of concentrates, non remunerative price for milk, procedural complications for insurance and subsidy and high cost of medicine and treatment were the major constraints in service delivery. SWOT Analysis revealed that, the cooperative had strong and weak sides with respect to livestock service delivery. Hence, to expand proven initiatives and strengthen good practice there is a need to improve upon the quality of the services and reduction in cost of services delivered so that farmers would be more content with the services of dairy cooperatives.